استخدام الهواتف الذكية وعلاقته بتنمية بعض المهارات الإدارية - عطية، نيبال فيصل عبدالحميد محمد; عمر، غادة عبدالقادر السيد; عبدالرؤف، مصطفي محمد الشيخ; أحمد، رابعة العدوية بسيوني أبو سيد (جامعة كفر الشيخ - كلية التربية النوعية, 2023)
يهدف البحث بصفة رئيسية إلى دراسة أثر استخدام الهواتف الذكية في تنمية المهارات الإدارية (إدارة الوقت-إدارة الطاقة الجهد-اتخاذ القرار-ترشيد الاستهلاك-البحث الإلكتروني). وقد أجري البحث علي: (٦٠) تلميذة بالصف الثاني الإعدادي مقسمين على مجموعتين الأولي تجريبية وعددهن (۳۰) تلميذة والثانية مجموعة ضابطة وعددهن (۳۰) تلميذة، وتم إعداد دليل المعلمة وكراسة نشاط التلميذة وفقا لاستخدام الهواتف الذكية، تم تطبيق أدوات البحث متمثلة في مقياس المهارات الإدارية، تفريغها وتبويبها وجدولتها وتحليلها إحصائيا باستخدام برنامج (SPSS) ويتبع هذا البحث المنهج التجريبي ذو التصميم شبة التجريبي، وأسفرت أهم النتائج عن وجود أثر وفاعلية لاستخدام الهواتف الذكية في تنمية المهارات الإدارية لتلميذات الصف الثاني الإعدادي، ووجود علاقه ارتباطية ذات دلالة إحصائية بين استخدام الهواتف الذكية والمهارات الإدارية لتلميذات الصف الثاني الإعدادي، وكانت أهم التوصيات البحث الاهتمام بالمناهج الدراسية والعمل على تطويرها من خلال استخدام الهواتف الذكية والتقنيات الحديثة، استخدام الهواتف الذكية في تدريس مادة الاقتصاد المنزلي والمواد الأخرى، عقد دورات تدريبية لمعلمات الاقتصاد المنزلي لتدريبهم على كيفية الاستفادة من الهواتف الذكية لتنمية مهارات التلميذات. The research mainly aims to study the impact of using smart phones on developing administrative skills (time management- energy and effort management- decision making- rationalization of consumption- electronic research). The research was conducted on: (60) female students in the second year of preparatory school, divided into two groups, the first an experimental group, numbering (30) students, and the second a control group, numbering (30) students. The teacher’s guide and the student’s activity booklet were prepared according to the use of smart phones, and then the research tools of In a cognitive test for administrative skills, then transcribed, tabulated, tabulated, and statistically analyzed using the SPSS program. This research follows the experimental method with a quasi-experimental design, The most important results resulted in the presence of an impact and effectiveness of the use of smart phones in developing administrative skills for second-year middle school students, and the existence of a statistically significant correlation between the use of smart phones and administrative skills for second year middle school students. The most important recommendations of the research were paying attention to the school curricula and working to develop them through the use of Smart phones and modern technologies, using smart phones in teaching home economics and other subjects, Holding a training course on home economics to train them on how to benefit from smart talents to develop female students’ skills.
Keywords: الاستراتيجيات التعليمية -- المهارات الإدارية -- الهواتف الذكية -- طلبة المدارس -- المناهج الدراسية